ANALISIS SISTEM PRESENSI BERBASIS GOOGLE APPS SCRIPT: STUDI KASUS TUTORIAL PAI-SPAI UPI - Ummara, Taufiq Wadi; Fahmi, I’zaz Dzul; Azis, Dwi Fauzan Muhammad; Arif, Wildan Zamaludin; Yulia, Hazza Erlina Putri; Hamidah, Siti (Universitas Hasyim Asy`ari, 2025)
An optimal attendance system is required to accurately record student attendance, which will ultimately affect their final grades. In the mentoring segment of the PAI-SPAI UPI Tutorial, a Google Apps Script-based attendance system implementing the Haversine formula is used. This research aims to analyse the attendance system to identify any issues that may cause data inaccuracies, rendering the system ineffective. The study employs qualitative and quantitative approaches, utilizing interviews, observations, literature reviews, and experiments. The results show that out of 5 Android devices and 5 iOS devices tested, 2 Android devices and 1 iOS device encountered issues preventing them from recording attendance. Additionally, the system's location accuracy and consistency were only 44.82%, which falls under the